Radiolabelling Pt-based quadruplex DNA binders via click chemistry. (15th December 2022) - Lo, Rainbow; Majid, Aatikah; Fruhwirth, Gilbert O.; Vilar, Ramon
Graphical abstract: Abstract: Guanine-rich sequences of DNA and RNA can fold into intramolecular tetra-helical assemblies known as G-quadruplexes (G4). Their formation in vivo has been associated to a range of biological functions and therefore they have been identified as potential drug targets. Consequently, a broad range of small molecules have been developed to target G4s. Amongst those are metal complexes with Schiff base ligands. Herein, we report the functionalisation of one of these well-established G4 DNA binders (based on a square planar platinum(II)-salphen complex) with two different radiolabelled complexes. An 111 In-conjugate was successfully used to assess its in vivo distribution in a mouse tumour model using single-photon emission computed tomography (SPECT) imaging. These studies highlighted the accumulation of this Pt-salphen- 111 In conjugate in the tumour.